Social Interaction Test between a Rat and a Robot: A Pilot Study. (15th January 2016) - del Angel Ortiz, Rusalky; Contreras, Carlos M.; Gutiérrez-Garcia, Ana G.; González, Montes Fernando M.
The social interaction test is based on spontaneous behaviour observed between pairs of animals, usually rodents. Commonly, the behaviour of one of the members in the dyad is related to the behaviour of its partner; therefore, making accurate predictions about behaviour is difficult, and the behaviour of the dyad cannot be controlled. In the present study, we programmed an e-puck robot with simple behavioural patterns, such as moving around a cage and following and approaching a rat. The results were analysed by comparing behaviour that was displayed by two groups of experimental rats towards different types of partners: (i) in the first group of experimental rats, they interacted with another group of rats and (ii) in the second group of experimental rats, they interacted with the e-puck robot. Our aim was to study the behaviour of experimental rats in the social interaction test when the interaction partner is a pre-programmed robot, in order to find out whether a rat is able to display social interaction activities in that context. Those activities were evaluated by a structured scheme of possible behaviours, quantified in categories according to currently well-accepted nomenclature and definitions. In order to achieve this goal, we compared the social and non-social behaviour displayed by the experimental rat in rat-rat and rat-robot interactions (such as approaching and following behaviour). We observed predominantly non-social behaviours, such as exploring the cage, when the experimental rats confronted either another rat or the robot. The experimental rats displayed similar periods of approaching, sniffing and crawling (social behaviour), exploring, being quiet, self-grooming and evading (non-social behaviour) in encountering both the rat and the robot. However, in the presence of the robot, the experimental rats displayed long periods of time spent in following, in contrast to short periods of immobility. In the present study, we explored a behavioural repertoire that was classified into the social and the non-social, in which the robot was usually able to elicit social behaviour from the rat. The results of our experiments open possibilities for additional studies on social interaction in robot-live rat dyads (e.g., in predator-prey models).